The Influence of Final Tax Rates and Investment Risk on Millennial Taxpayers' Interest in Investing in the Capital Market: Pengaruh Tarif Pajak Final dan Risiko Investasi terhadap Minat Berinvestasi Pasar Modal oleh Wajib Pajak Milenial - Ida Ayu Diah Kartika Diva Maheswari; Kadek Wulandari Laksmi (Jurnal Akuntansi, Keuangan dan Perpajakan, 2026)
This study examines the effect of the final tax rate and investment risk on the investment interest of millennial taxpayers in the capital market in Denpasar City. A quantitative approach was employed using primary data collected through questionnaires distributed to 100 respondents selected through purposive sampling. The data were analyzed using multiple linear regression with the assistance of SPSS. The results indicate that the final tax rate and investment risk have a positive and significant influence on investment interest. These findings suggest that clear tax policies and a proper understanding of investment risk can encourage greater investment participation among millennial taxpayers in the capital market. AbstrakPenelitian ini bertujuan menguji pengaruh tarif pajak final dan risiko investasi terhadap minat berinvestasi wajib pajak milenial di pasar modal di Kota Denpasar. Penelitian menggunakan pendekatan kuantitatif dengan data primer yang diperoleh melalui penyebaran kuesioner kepada 100 responden yang dipilih menggunakan teknik purposive sampling. Analisis data dilakukan dengan regresi linier berganda menggunakan SPSS. Hasil penelitian menunjukkan bahwa tarif pajak final dan risiko investasi berpengaruh positif dan signifikan terhadap minat berinvestasi, sehingga kepastian kebijakan perpajakan serta pemahaman risiko dapat mendorong peningkatan partisipasi investasi milenial di pasar modal.